Pengaruh Faktor Risiko Terjadinya Katarak Terhadap Katarak Senil Pada Petani di Wilayah Kerja Puskesmas Tempurejo Kabupaten Jember - Agung Sudrajat; Al Munawir; Supangat Supangat (Pascasarjana Universitas Jember, 2021)
Eye health is important in achieving the quality of human resources in order to improve the quality of human life in the context of realizing a healthy, productive, and physically and mentally prosperous Indonesian society. Cataract is a disorder of the eye in which the lens of the eye becomes cloudy due to hydration of the lens (addition of fluid), denaturation of lens proteins or occurs due to both. The purpose of this study was to analyse the effect of cataract risk factors on the occurrence of senile cataracts in farmers in the Tempurejo Community Health Center, Jember Regency. The type of research used is observational analytic with case control research design. The population in this study was cataract cases based on the sensory health record files at the Tempurejo Health Center and farmers living in the working area of the Tempurejo Health Center with a simple number of 98 farmers, with a case sample of 48 farmers and a control sample of 48 farmers. Determination of the research sample using purposive sampling technique. The results of the study on farmers showed that female farmers 2.8 times (95%C1 1,221-6,423), farmers with low education and knowledge 2.7 times (95%C1 1,163-6,552) and 2.7 times (95%C1 1,217-6,366), farmers with socioeconomic less than 3.2 times (95%C1 1.309-7.898). Farmers have a history of hypertension 1.9 times (95%C1 0.764-5.081), farmers with ex-smoker/smoker status 1.6 times (95%C1 0.740-3.805) farmers work outside >4 hours per day 2.8 times (95%C1 1.189-6.866). The conclusion of this study, there is an effect of gender on senile cataract, there is an effect of education level and level of knowledge on senile cataract, there is a socio-economic effect on senile cataract, there is no effect of a history of hypertension on senile cataract, there is no effect of smoking habits on senile cataract, and There is an effect of working outside the building on senile cataract. Women farmers are advised to reduce the intensity of exposure to ultraviolet light. In addition, farmers should prioritize the use of PPE when working.